2013
DOI: 10.1186/1939-4551-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Insights, attitudes, and perceptions about asthma and its treatment: findings from a multinational survey of patients from Latin America

Abstract: BackgroundIn 2011 the Latin America Asthma Insight and Management (LA AIM) survey explored the realities of living with asthma. We investigated perception, knowledge, and attitudes related to asthma among Latin American asthma patients.MethodsAsthma patients aged ≥12 years from four Latin American countries (Argentina, Brazil, Mexico, Venezuela) and the Commonwealth of Puerto Rico responded to questions during face-to-face interviews. A sample size of 2,169 patients (approximately 400 patients/location) provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
80
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 10 publications
8
80
2
5
Order By: Relevance
“…An investigation developed in China, with the application of the questionnaire Knowledge, Attitude and Practice with 2,960 parents/guardians, concluded that low scores in questions related to knowledge, attitudes, and practices reflect on childhood asthma control parameters (24) . Another study from Latin America with 2,169 patients aged 12 years old or older with asthma revealed that 60% of the interviewed people declared that their disease was controlled or well controlled, but only 8% fulfilled the Global Initiative for Asthma criteria for well-controlled asthma (25) . Non-controlled asthma results in visits to emergency units and hospital admissions (26) .…”
Section: Discussionmentioning
confidence: 99%
“…An investigation developed in China, with the application of the questionnaire Knowledge, Attitude and Practice with 2,960 parents/guardians, concluded that low scores in questions related to knowledge, attitudes, and practices reflect on childhood asthma control parameters (24) . Another study from Latin America with 2,169 patients aged 12 years old or older with asthma revealed that 60% of the interviewed people declared that their disease was controlled or well controlled, but only 8% fulfilled the Global Initiative for Asthma criteria for well-controlled asthma (25) . Non-controlled asthma results in visits to emergency units and hospital admissions (26) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous surveys of patients with asthma (notably AIR [6,7,16], AIM [8,17,18,32] and REALISE [9,10]) have emphasised patients' lack of both understanding of treatment and belief in its effectiveness when used in accordance with guidelines. Patients also communicated low expectations of achievable control and a high tolerance of symptoms, as demonstrated by the discrepancy between patients' assessments of their asthma control and the extent of their control according to guideline criteria [6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Patients also communicated low expectations of achievable control and a high tolerance of symptoms, as demonstrated by the discrepancy between patients' assessments of their asthma control and the extent of their control according to guideline criteria [6][7][8][9][10]. This is despite the demonstration that guidelinedefined control is achievable in most patients [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations